2018
DOI: 10.29262/ram.v65i3.373
|View full text |Cite
|
Sign up to set email alerts
|

The pragmatic role of nasal cytology: a point-of-care testing to implement precision medicine in clinical practice

Abstract: Nasal cytology provides quick information about phenotype and endotype and can be repeated during follow-up to assess post-treatment changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Gelardi et al 6 identified a diagnostic instrumental method in nasal cytology (NC) that could be used in the differential diagnosis of AR and in the longitudinal evaluation of inflammatory state of nasal mucous in adults. The authors underlined that this reliable, rapid and easy to perform test, at a low cost, has all the requisites to be defined as POCT.…”
Section: Point Of Test Care In Allergic Rhinitismentioning
confidence: 99%
“…Gelardi et al 6 identified a diagnostic instrumental method in nasal cytology (NC) that could be used in the differential diagnosis of AR and in the longitudinal evaluation of inflammatory state of nasal mucous in adults. The authors underlined that this reliable, rapid and easy to perform test, at a low cost, has all the requisites to be defined as POCT.…”
Section: Point Of Test Care In Allergic Rhinitismentioning
confidence: 99%
“…Polyallergic patients with AR experienced significantly more severe nasal symptoms than monoallergic ones and showed higher infiltration of eosinophilic and inflammatory mast cells in nasal cytology. Thus, the inflammatory pattern in nasal cytology may be a useful instrument to better characterize the phenotypes and endotypes of allergic and nonallergic rhinitis and realize personalized treatments 34…”
Section: United Airway Disease As a Model Of Diagnosis And Care In Sementioning
confidence: 99%
“…Two types of non-allergic rhinitis of joined different cells infiltration are also distinguished, as non‐allergic rhinitis eosinophilic mast cell syndrome (NARESMA), in addition to the important eosinophilic infiltrate, in which a mast cell component (> 10% of total nasal cells) is detectable and non‐allergic rhinitis with mast cells (NARMA) characterized by the isolated mast cell infiltration (> 10% of total nasal cells). It is stressed that there is a need for further studies on the above-mentioned syndromes to determine the appropriate procedure to interpret the cytological tests in relation to the clinical picture of the patients and to introduce an effective treatment to avoid any complications 1 , 19 – 21 .…”
Section: Introductionmentioning
confidence: 99%